2020
DOI: 10.1111/eva.13132
|View full text |Cite
|
Sign up to set email alerts
|

Testing for population differences in evolutionary responses to pesticide pollution in brown trout (Salmo trutta)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Parental effects on embryo and larval performance have been repeatedly analyzed in other salmonids, usually based on fullfactorial breeding experiments with sufficient replication on the maternal and the paternal sides and large numbers of embryos that were often singly reared as in the present study (recent examples include Clark et al, 2016;Forest et al, 2016;Marques da Cunha et al, 2019;Nusbaumer et al, 2021c). Such experiments allow separating and quantifying the variance components and hence testing, for example, for the evolutionary potential of natural populations to adapt to changing environments (Lynch and Walsh, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental effects on embryo and larval performance have been repeatedly analyzed in other salmonids, usually based on fullfactorial breeding experiments with sufficient replication on the maternal and the paternal sides and large numbers of embryos that were often singly reared as in the present study (recent examples include Clark et al, 2016;Forest et al, 2016;Marques da Cunha et al, 2019;Nusbaumer et al, 2021c). Such experiments allow separating and quantifying the variance components and hence testing, for example, for the evolutionary potential of natural populations to adapt to changing environments (Lynch and Walsh, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, eggs were rinsed for 30 s under cold running tap water (4 L/min) in a sterilized tea strainer before being distributed singly in 24 well plates (Falcon, BD Biosciences, Allschwil, Switzerland) filled with 1.8 mL of autoclaved standardized water (OECD, 1992), and incubated at 4.5 • C in a 12 h:12 h light-dark cycle (to simplify monitoring and minimize variation of light conditions) until 14 days post-hatching as in von Siebenthal et al (2009). Under these environmental conditions, embryo mortality until hatching is typically < 3% in similar-sized eggs of brown trout (Nusbaumer et al, 2021c). We considered a short rinsing of the eggs necessary because we had previously observed that not rinsing eggs before incubation in 24-well plates can lead to very high embryo mortalities (Wedekind, unpublished observations).…”
Section: Monitoring Of Embryos and Larvaementioning
confidence: 99%
“…Concentrations as low as 1.1 µg/L of S‐metolachlor increased mortality and slowed juvenile growth in marbled crayfish ( Procambarus virginalis ; Velisek et al, 2019). Also, Nusbaumer et al (2021) found reduced growth rates in newly hatched brown trout ( Salmo trutta ) exposed to 0.07 and 0.25 µg/L of S‐metolachlor. Surprisingly, little is known about the effects of metolachlor at sublethal concentrations in amphibians (but see Hayes et al, 2006; Relyea, 2009; Spolyarich et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…This allows for full-factorial treatments and testing for interesting 2-way or 3-way interactions between parental and environmental factors. Full-factorial crosses can also be used to disentangle the different variance components that contribute to important commercial traits (Colihueque, 2010; Ødegård et al, 2011) and they give insights into, for example, the potential of ‘good-genes’ sexual selection (Wedekind et al, 2008, 2001), the evolutionary potential of populations to react to chemical pollutants (Marques da Cunha et al, 2019; Nusbaumer et al, 2021b), pollution by nanoparticles (Clark et al, 2016; Yaripour et al, 2021), reactions to climate change (Muñoz et al, 2015), or to pathogens (Ødegård et al, 2011). Pathogens might influence hatching time, survival and growth of embryos (Pompini et al, 2013; von Siebenthal et al, 2009; Wilkins et al, 2017), and maternal environmental effects (egg size and content, including various carotenoids) might affect embryonic tolerance (Wilkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%